STRENGTHENING COMMUNITY CHARACTER AND LITERATURE IN HANDLING STUNTING THROUGH VILLAGE DIGITALIZATION IN GUWOSARI SUB-DISTRICT - An-Nisa Apriani; Kana Safrina Rouzi; Mufida Awalia Putri; Yhona Paratmanitya; Defia Ifsantin Maula; Endi Rohaendy; Sukati Sukati; Laelatul Badriah; Dadang Heksaputra; Rizky Saputri (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Mataram, 2023)
TPA cadres' understanding toward the role of Quran literacy, Living Values Education Program (LVEP), business & economy and literacy digitization in stunting handling is still inadequate. Strengthening their literacy in handling stunting is needed to prevent stunting problems in the TPA environment. This community service activities aim to increase the understanding of TPA cadres pertainin the Quran literacy, LVEP, business, economics, and digitalization as one of the programs to strengthen community literacy in stunting control. The main activity of the workshop is in the form of training using the lecture method, question and answer, and discussion. The community service activities are carried out through three stages, namely preparation, implementation, and evaluation. The participation and enthusiasm of the TPA cadres in the activity was very good, the partner group contributed actively in the workshops on strengthening community character and literacy in handling stunting through village digitization in the Guwosari sub-district.